Original articleCirculated CD4+CD28- lymphocytes rate and their cytotoxicity and morphological parameters of internal carotid artery atheromatous plaques in patients with atherosclerosis-related ischemic stroke - Masztalewicz, Marta; Nowacki, Przemysław; Bajer-Czajkowska, Anna; Kotfis, Katarzyna; Biernawska, Jowita; Safranow, Krzysztof; Żukowski, Maciej; Gutowski, Piotr (Folia Neuropathologica, 2013)
Background: The question about the role of CD4 + CD28 – lymphocytes in the pathogenesis of atherosclerosis-related ischemic stroke is still open. Material and methods: The study included patients, who underwent endarterectomy of internal carotid arteries. The group consisted of patients after stroke and ones without previous stroke. The histopathologic examination of obtained plaques has been performed. The percentage of CD4 + CD28 – lymphocytes in peripheral blood and their cytotoxicity has been assessed for each patient. Results: The global percentage of CD4 + CD28 – lymphocytes in blood was higher in the group of patients with plaques where connective tissue fibers consisted significantly of collagen fibers. The cytotoxicity of analysed cells related to less plaques calcification and presence of cholesterol crystals in the plaque. A multifactor regression of dependent variable presented the last relationship above as a only strong. Conclusions : CD4 + CD28 – cytotoxic lymphocytes seem to be involved in carotid atherosclerotic plaques development. Intraplaque cholesterol deposits may contribute to this process.